Strategi Pemerintah Desa Dalam Pengembangan Objek Wisata Alam Pantai Cemara Indah Desa Gosong Telaga Kecamatan Aceh Singkil Utara, Kabupaten Aceh Singkil - Toni Abasri Padang; Maringan Sinambela; Yulia K.S. Sitepu; Robert Juni Tua Sitio; Ade Putera Arif Panjaitan (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to determine the Village Government's strategy in developing the Cemara Indah Beach tourist attraction, Gosong Telaga Village, North Singkil District, Aceh Singkil Regency. The type of research used is qualitative research. The sample in this research was the Cemara Indah Gosong Telaga Beach tourist attraction. The results of the research show that the Village Government's strategy in developing Cemara Indah Beach, Gosong Telaga Village, North Singkil District, Aceh Singkil Regency is more focused on creating promotional media such as creating social media such as Facebook, Instagram, WEBSite, Tiktok and Banners. This method is one of the promotional methods used. can attract the attention of visitors to visit Cemara Indah Gosong Telaga Beach. Of the various aspects that provide opinions specifically for the Gosong Telaga Village Government in the development of the Cemara Indah Beach tourist attraction, there are several inhibiting factors that researchers found from statements and those felt by the Gosong Telaga Village Government, including promotions, facilities, tickets that are too expensive for visitors, There are other tours that are still free